Economic Status to Students' Physical Education Learning in Elementary School, Padang City - Deri Putra; Debby Indah; Ikhbal Elkadiowand; Darni Darni; Willadi Rasyid; Fitri Agung Nanda; Ali Munir (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
This research is based on the school's fact that student learning outcomes are still low from the previous semester, student scores are still below average or below graduation standards. The purpose of this research is to see how big the contribution of nutritional status and economic status to students' physical education. The population in this study were students27 Ulak Karang Elementary School, Padang Citya total of 131 people. The sampling technique was purposive sampling, so the sample in this study was set at 30 people, namely class V and VI girls only. To obtain research data, NHCS was used, a questionnaire to reveal the economic status of parents and learning outcomes from report cards. The data obtained were analyzed by simple product moment correlation, and continued with multiple correlations to get the relationship between the three variables, for the contribution was carried out with the determinant coefficient. The results of the analysis show that, there is a significant relationship between nutritional status and physical education learning outcomes where rcount 0.385 > rtable 0.361 at = 0.05. There is a significant relationship between Economic Status and Physical Education learning outcomes where rcount 0.488 > rtable 0.361 at =0.05.There is a joint relationship between nutritional status and economic status on student physical education learning outcomes27 Ulak Karang Elementary School, Padang Citywhere Rcount 0.555 > Rtable 0.361 at =0.05. Thus, it can be concluded that the economic status in learning, especially physical education for elementary school students in the city of Padang, plays an important role in supporting nutritional health and can provide benefits and education to educators and guardians of students in implementing nutritional and economic status for physical education. Keywords: Economic Status, Physical Education, Elementary School.